PENGEMBANGAN MATERI MENGENAI PENGEMBANGAN DIRI (MINAT BAKAT) - Mutiara Aulia Aghni; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research conducted to developing the material on the students’ selfdevelopment (interest talents) at nineth grade of senior high school, and the description ofadvisability has been reviewed from aspects the clarity of material, material scientific,supporting images, the latest material, completeness of the material, and supporting videosor games. This study is the research development with analysis data technique by usingdatas’ validity. The source of the data obtained from advisor 1, advisor 2, 4 of counselingteachers and 27 of students at nineth grade MIA 1 of SMA Negeri 1 Pekanbaru. Theresults showed that the self-development material has been self development (interesttalents) with the overall quality of the material aspects Very Good . So that the material isfit for use by teachers guidance and counseling in schools.Key word : the Guidance and Counseling materials, self development (interest talents)